Clinical and imaging assessment and treatment of hallux valgus. (January 2020) - Heineman, Nathan; Liu, George; Pacicco, Thomas; Dessouky, Riham; Wukich, Dane K; Chhabra, Avneesh
Hallux valgus is a common condition estimated to affect as many as 23% of adults. The condition is associated with a variety of debilitating symptoms leading to significant morbidity and quality of life issues. Proper evaluation of this deformity and the timely management of its symptoms can improve hallux valgus-related symptomatology and quality of life. The most commonly used and readily reproduced measurements for assessing hallux valgus are the inter-metatarsal angle and the hallux valgus angle. These angles are helpful for choosing and planning surgical intervention for patients who fail initial conservative measures with distal osteotomies reserved for mild or moderate hallux valgus and proximal osteotomies indicated for more moderate to severe deformities. After reading this review article, readers will gain knowledge of the etiopathogenesis of hallux valgus, measurement parameters, and treatment strategies with representative case examples.